IMPLEMENTATION OF ETHICS MANAGEMENT NOWADAYS IN THE ROMANIAN UNIVERSITY ENVIRONMENT - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2018)
The paper shows that, at the present moment, the management of ethics in the academic environment is the coordination of all elements related to the moral life of a university. The last decades have insistently imposed on public awareness the importance of taking into account the ethical dimension of the life of universities. Ethical codes, ethics committees and commissions, ethical audits, ethical education of staff, techniques to create an institutional culture of a moral nature have all become increasingly widespread. The University respects the dignity of each of its members and promotes academic integrity on ethical principles. Its members are committed to contributing to the democratic development and prosperity of society. The University is an institution whose goals, valid for each of its members, include development and professional affirmation, the evolution of knowledge and research in the conditions of respect for the rule of law and human rights. I think that the values and principles that universities have to promote in particular, and whose actual achievement is sought to ensure, are: academic freedom, personal autonomy, justice and equity, merit, professionalism, honesty and intellectual integrity, transparency, respect and tolerance, responsibility, goodwill and care. I also think that "institutionalization of ethics" in academia is a new reality for which we all must be prepared.